(untitled) - Midley, Dale (Hoboken, N.J., 2005)
In Golden Circle Secrets, father-and-son team Dale and Ben Midgley show management and the sales team how to achieve consistent success in sales. Based on a unique new strategy that responds to customer values and expectations, the Midgleys reveal how sales and management are inseparable components of sales success that must work in tandem to produce consistent results for an organization. Sales increase when management and its sales force are on the same page. The "golden circle" is based on a customer-oriented business system specifically designed to help companies attract and satisfy customers and energize employees, while maintaining a consistently healthy level of profits.
Keywords: Sales management,Success in business,Customer relations